Electrode, secondary battery including the same, and method of manufacturing the same

By adding fluoroelastomer to the dry electrode and adopting low shear kneading and crushing processes to form an electrode layer with high flexibility and bending resistance, the existing dry electrodes are solved in the manufacturing process of degradation and prone to fracture.

CN119404319APending Publication Date: 2025-02-07LG ENERGY SOLUTION LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380035118.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-20
Filing Date
2023-04-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

During the manufacturing process, existing dry electrodes are prone to produce fine powders with smaller particle sizes, resulting in degradation of mechanical and electrochemical properties, and the flexibility provided by traditional technology is insufficient and easy to break.

Method used

The electrode layer consisting of active material, conductive material, adhesive and fluoroelastomer is adopted, and a uniform mixed powder is formed by a low shear kneading process and crushing step, followed by calendering to form an electrode film and laminated to the current collector superior.

Benefits of technology

The flexural resistance and flexibility of the electrode are improved, the risk of fracture is reduced, and the processing performance and production processability of the electrode are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404319A_ABST
    Figure CN119404319A_ABST
Patent Text Reader

Abstract

Disclosed is an electrode comprising: an electrode current collector; and an electrode layer disposed on the electrode current collector and including an active material, a conductive material, a binder, and a fluoroelastomer; and the bending resistance of the electrode is 10 mm (phi) or less. A secondary battery including the electrode and an energy storage system are also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrode, a secondary battery including the electrode, and a method of manufacturing the same. In particular, the present disclosure relates to an electrode with improved flexibility, a secondary battery including the same, and a method of manufacturing the same.

[0002] This application claims the priority of Korean Patent Application No. 10-2022-0049213 filed in Korea on April 20, 2022, the disclosure of which is incorporated herein by reference. Background Art

[0003] Due to the rapid increase in the use of fossil fuels, there is an increasing demand for the use of alternative and clean energy. As part of an attempt to meet this demand, the most active area of ​​research is the field of power generation and storage using electrochemistry. At present, typical examples of electrochemical devices that utilize electrochemical energy include secondary batteries, and their application range has been gradually expanding. Recently, as a representative of such secondary batteries, lithium secondary batteries have been used not only as an energy source for mobile instruments, but also as a power source for electric vehicles and hybrid vehicles, which can replace vehicles such as gasoline and diesel vehicles that use fossil fuels and are considered to be one of the main causes of air pollution. In addition, by forming a grid, the application of such lithium secondary batteries has even been expanded to an auxiliary power source for electricity.

[0004] The process of manufacturing such a lithium secondary battery is roughly divided into the following three steps: an electrode forming step, an electrode assembly forming step, and an aging step. The electrode forming step is further divided into an electrode mixture mixing step, an electrode coating step, a drying step, a pressing step, a slitting step, a winding step, or the like.

[0005] Among these steps, the electrode mixture mixing step is a step of mixing the components for forming an electrode active layer that actually performs an electrochemical reaction in the electrode. Specifically, the electrode active material as a basic element of the electrode is mixed with other additives including a conductive material and a filler, a binder for bonding between powder particles and for adhering to a current collector, a solvent for imparting viscosity and dispersing the powder, or the like to prepare a slurry having fluidity.

[0006] Then, an electrode coating step of applying the slurry to a current collector having conductivity and a drying step of removing a solvent contained in the electrode mixture are performed, and then the resulting electrode is pressed to a predetermined thickness.

[0007] Meanwhile, as the solvent contained in the electrode mixture evaporates during the drying step, defects such as pinholes or cracks are generated in the initially formed electrode active layer. In addition, due to the different evaporation rates of the solvent, the active layer is not dried uniformly at its inside and outside, so that powder floating phenomenon occurs. In other words, the powder present in the earlier dried part will float up and form a gap with the relatively later dried part, resulting in a decrease in electrode quality.

[0008] Therefore, in order to solve the above problems, a drying device that can uniformly dry the inside and outside of the active layer and control the evaporation rate of the solvent has been considered. However, this drying device is expensive, requires a lot of cost and time to operate, and is therefore disadvantageous in terms of manufacturing processability.

[0009] Therefore, active research has recently been conducted to fabricate dry electrodes without using any solvent.

[0010] Generally, a dry electrode is obtained by laminating a self-supporting film including an active material, a binder, a conductive material, or the like on a current collector and forming into a film shape.

[0011] In this conventional dry electrode, an active material, a carbonaceous material as a conductive material, and a binder capable of fibrillation are mixed by using a mixer or the like, the binder is fibrillated by a high shear mixing step such as jet milling, and then the resulting mixture is calendered into a film shape to provide a self-supporting film. Then, the self-supporting film obtained after calendering is laminated on a current collector to obtain a dry electrode.

[0012] However, when such a high shear mixing step is applied to highly brittle active materials, a large amount of fine powder with a small particle size is generated, resulting in a decrease in mechanical or electrochemical properties. When high shear mixing is excessively performed, the resulting binder fibers may be cut, resulting in a decrease in the flexibility of the self-supporting film. In addition, during the jet milling step, the components may adhere to the inside of the device, thereby interrupting the flow of high-pressure air and causing a flow path clogging problem, which is not conducive to large-scale production.

[0013] In addition, the conventional technology for manufacturing dry electrodes provides low flexibility, so there is a problem that the dry electrodes are easily broken.

[0014] Therefore, there is an urgent need to develop a technology for manufacturing dry electrodes that can solve the above problems. Summary of the invention

[0015] Technical issues

[0016] The present disclosure is designed to solve the problems of the prior art, and thus the present disclosure aims to provide an electrode with improved flexibility, a secondary battery including the electrode, and a method of manufacturing the same.

[0017] Technical Solution

[0018] In one aspect of the present disclosure, an electrode according to any one of the following embodiments is provided.

[0019] According to a first embodiment of the present disclosure, there is provided an electrode, the electrode comprising: an electrode current collector; and an electrode layer, the electrode layer being disposed on the electrode current collector and comprising an active material, a conductive material, a binder, and a fluoroelastomer; and

[0020] The bending resistance of the electrode is 10 mm (Ø) or less.

[0021] According to a second embodiment of the present disclosure, there is provided an electrode as defined in the first embodiment, wherein the binder is fibrillated to bind the active material, the conductive material and the fluoroelastomer.

[0022] According to a third embodiment of the present disclosure, an electrode as defined in the first or second embodiment is provided, wherein the fluoroelastomer includes vinylidene fluoride based rubber (FKM), tetrafluoroethylene propylene based rubber (FEPM), tetrafluoroethylene-perfluoromethyl vinyl ether based rubber (FFKM), tetrafluoroethylene based rubber (TFE), or two or more thereof.

[0023] According to a fourth embodiment of the present disclosure, there is provided an electrode as defined in any one of the first to third embodiments, wherein a weight ratio of the binder to the fluoroelastomer is 40:60 to 80:20.

[0024] According to a fifth embodiment of the present disclosure, there is provided an electrode as defined in any one of the first to fourth embodiments, the electrode having a bending resistance of 2 mm to 8 mm (Φ).

[0025] According to a sixth embodiment of the present disclosure, there is provided the electrode as defined in any one of the first to fifth embodiments, wherein the bending resistance of the electrode is evaluated according to the method of the test standard JIS K5600-5-1.

[0026] According to a seventh embodiment of the present disclosure, there is provided an electrode as defined in any one of the first to sixth embodiments, wherein the bending resistance of the electrode is evaluated by the following steps:

[0027] A rectangular electrode sample with a size of 100 mm × 50 mm was prepared;

[0028] preparing test rods each having a diameter of 2, 3, 4, 5, 6, 8, 10, 12, 16, 20, 25 or 32 mm, selecting the test rod having the largest diameter and bringing the electrode sample into contact with the test rod, and judging whether cracks are generated in the mixture film of the electrode sample when both ends of the electrode sample are lifted; and

[0029] If no cracks are generated in the previous step, select a test rod with the second largest diameter and judge whether cracks are generated in the mixture film of the electrode sample in the same manner as the previous step. Repeat this step to determine the minimum diameter value of the test rod that will not cause cracks in the mixture film of the electrode sample as the bending resistance.

[0030] According to an eighth embodiment of the present disclosure, there is provided the electrode as defined in any one of the first to seventh embodiments, wherein the crystallinity of the binder is 10% or less.

[0031] According to a ninth embodiment of the present disclosure, there is provided an electrode as defined in any one of the first to eighth embodiments, wherein the binder includes a fluorine-containing binder, the QBR (Quantified Binder Ratio) of the electrode layer is 1.1 or less, and the QBR is defined by the following formula:

[0032] QBR=Bs / Bf,

[0033] Wherein Bs represents the average value of the fluorine content in the surface area of ​​the electrode layer within the range from the outermost surface of the electrode layer to 15% of the total thickness of the electrode layer, and Bf represents the average value of the fluorine content in the bottom area of ​​the electrode layer within the range from the electrode layer interface facing the current collector to 15% of the total thickness of the electrode layer.

[0034] According to a tenth embodiment of the present disclosure, there is provided an electrode as defined in any one of the first to ninth embodiments, wherein the conductive material includes activated carbon, graphite, carbon black, Ketjen black, carbon nanotubes, or two or more thereof.

[0035] According to an eleventh embodiment of the present disclosure, there is provided an electrode as defined in any one of the first to tenth embodiments, wherein the binder includes polytetrafluoroethylene (PTFE).

[0036] According to a twelfth embodiment of the present disclosure, there is provided an electrode as defined in any one of the first to eleventh embodiments, wherein the active material is a positive electrode active material or a negative electrode active material.

[0037] According to a thirteenth embodiment of the present disclosure, there is provided an electrode as defined in any one of the first to twelfth embodiments, wherein the content of the active material is 80 to 98 parts by weight, the content of the conductive material is 0.5 to 10 parts by weight, the content of the binder is 0.5 to 5 parts by weight, and the content of the fluoroelastomer is 0.1 to 5 parts by weight.

[0038] According to a fourteenth embodiment of the present disclosure, there is provided an electrode as defined in any one of the first to thirteenth embodiments, wherein the current collector further includes a conductive primer layer on at least one surface thereof.

[0039] According to a fifteenth embodiment of the present disclosure, there is provided an electrode as defined in any one of the first to fourteenth embodiments, wherein the electrode layer is derived from a dry electrode film.

[0040] According to a sixteenth embodiment of the present disclosure, there is provided a method for manufacturing an electrode as defined in any one of the first to fifteenth embodiments, the method comprising the following steps:

[0041] preparing a mixture comprising an active material, a conductive material, a binder, and a fluoroelastomer;

[0042] kneading the mixture at 70° C. to 200° C. under a pressure equal to or higher than ambient pressure to prepare a mixture mass;

[0043] pulverizing the mixture agglomerate to obtain a mixed powder for an electrode;

[0044] introducing a mixed powder for an electrode between a plurality of rollers to perform calendaring, thereby forming an electrode film; and

[0045] The electrode film is laminated onto a metal current collector.

[0046] According to a seventeenth embodiment of the present disclosure, there is provided a method for manufacturing an electrode as defined in the sixteenth embodiment, wherein the step of kneading the mixture to prepare a mixture mass is performed in a kneader at a pressure equal to or higher than ambient pressure.

[0047] According to an eighteenth embodiment of the present disclosure, there is provided the method for manufacturing an electrode as defined in the sixteenth or seventeenth embodiment, wherein a pressing ratio of the electrode film is 20% or less.

[0048] According to a nineteenth embodiment of the present disclosure, there is provided a secondary battery including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein at least one of the positive electrode and the negative electrode is an electrode as defined in any one of the first to fifteenth embodiments.

[0049] According to a twentieth embodiment of the present disclosure, there is provided an energy storage system including the secondary battery as defined in the nineteenth embodiment as a unit battery.

[0050] Beneficial Effects

[0051] The electrode is basically brittle and is easily broken when impacted or deformed. The electrode according to an embodiment of the present disclosure includes a fluoroelastomer with high elastic deformation performance added to the particles used to make the dry electrode, thereby improving the performance of the electrode breaking when impacted or deformed. In this way, an electrode with excellent flexibility (bending resistance) and good handling performance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The accompanying drawings illustrate preferred embodiments of the present disclosure and, together with the foregoing disclosure, are used to provide a further understanding of the technical features of the present disclosure. Therefore, the present disclosure is not to be construed as being limited to the accompanying drawings.

[0053] Figure 1 is a schematic diagram showing an electrode according to an embodiment of the present disclosure.

[0054] Figure 2 Schematic diagram showing calculation of the QBR value of the electrode layer.

[0055] Figure 3a and Figure 3b is a schematic diagram illustrating a process for manufacturing an electrode film applied to an electrode assembly according to an embodiment of the present disclosure.

[0056] Figure 4 is a schematic diagram illustrating an electrode lamination step according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0057] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings.

[0058] Prior to the description, it should be understood that the terms used in the specification and the appended claims should not be interpreted as being limited to the general meaning and dictionary meaning, but should be interpreted based on the meaning and concepts corresponding to the technical aspects of the present disclosure on the basis of the principle allowing the inventor to appropriately define the terms for the best interpretation.

[0059] The terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the present disclosure.As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0060] It will be further understood that when the terms “include” and / or “comprising” or “include” and / or “comprising” are used in this specification, they do not exclude the presence of other elements but specify the additional presence of other elements unless otherwise stated.

[0061] In one aspect of the present disclosure, there is provided an electrode comprising:

[0062] an electrode current collector; and

[0063] an electrode layer disposed on the electrode current collector and comprising an active material, a conductive material, a binder, and a fluoroelastomer; and

[0064] The bending resistance of the electrode is 10 mm (Ø) or less.

[0065] According to an embodiment of the present disclosure, the electrode may be a positive electrode or a negative electrode, and the active material may be a positive electrode active material or a negative electrode active material.

[0066] For example, the positive electrode active material includes, but is not limited to: lithium transition metal oxides; lithium metal iron phosphate, lithium nickel manganese cobalt oxide; lithium nickel manganese cobalt oxide partially substituted by other transition metals; or two or more thereof. Specific examples of positive electrode active materials may include, but are not limited to: layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or those compounds substituted by one or more transition metals; lithium manganese oxides such as Li 1+x Mn 2- x O4 (where x is 0-0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, or Cu2V2O7; 1-x M x O2 (wherein M is Co, Mn, Al, Cu, Fe, Mg, B, or Ga, and x is 0.01-0.3) represented by a Ni-type lithium nickel oxide; represented by a chemical formula LiMn 2-x M x Lithium manganese composite oxide represented by the chemical formula Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu, or Zn); lithium metal phosphate LiMPO4 (wherein M is Fe, CO, Ni, or Mn); lithium nickel manganese cobalt oxide Li 1+x (Ni a Co b Mn c ) 1-xO2 (where x ranges from 0 to 0.03, a ranges from 0.3 to 0.95, b ranges from 0.01 to 0.35, c ranges from 0.01 to 0.5, and a + b + c = 1); lithium nickel manganese cobalt oxide partially substituted by aluminum (lithium nickel manganese cobalt aluminum oxide) Li a [Ni b Co c Mn d Al e 1-f M 1 f O2 (where M 1 is at least one selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S, 0.8 ≤ a ≤ 1.2, 0.5 ≤ b ≤ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≤ e ≤ 0.1, 0 ≤ f ≤ 0.1); disulfide compounds; Fe2(MoO4)3; or the like. In particular, the lithium nickel manganese cobalt aluminum oxide may include Li[Ni 0.73 Co 0.05 Mn 0.15 Al 0.02 O2) or the like.

[0067] In addition, non - limiting examples of the negative electrode active material include: carbon, such as non - graphitizable carbon or graphite - based carbon; metal composite oxides, such as Li x Fe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), and Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, elements of Groups 1, 2, and 3 of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8); lithium metal; lithium alloys; silicon - based alloys; tin - based alloys; silicon - based oxides, such as SiO, SiO / C, and SiO2; metal oxides, such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; and conductive polymers, such as polyacetylene; Li - Co - Ni - based materials; or the like.

[0068] According to an embodiment of the present disclosure, the electrode may be a positive electrode. Thus, in particular, the active material may be a positive electrode active material. More particularly, the positive electrode active material may include lithium transition metal oxides, lithium nickel manganese cobalt oxides, lithium nickel manganese cobalt oxides partially substituted by Al or another transition oxide, lithium iron phosphate, or the like. ​

[0069] The conductive material is not particularly limited as long as it has conductivity and does not cause any chemical changes in the corresponding battery. Specific examples of conductive materials include: graphite, such as natural graphite or artificial graphite; carbonaceous materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black or carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum or silver; needle-shaped or dendrite-shaped conductive whiskers (Whisker), such as zinc oxide whiskers, calcium carbonate whiskers, titanium dioxide whiskers, silicon oxide whiskers, silicon carbide whiskers, aluminum borate whiskers, magnesium borate whiskers, potassium titanate whiskers, silicon nitride whiskers, silicon carbide whiskers or aluminum oxide whiskers; conductive metal oxides, such as titanium dioxide; conductive polymers, such as polyphenyl derivatives; or the like. These conductive materials can be used alone or in combination. Particularly, the conductive material may include at least one selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes, and more particularly activated carbon, so as to uniformly mix the conductive material and improve conductivity.

[0070] Adhesive can include fluorine-containing adhesive, fluorine-free adhesive or two or more thereof. Fluorine-containing adhesive can include fluorine-containing polymer, and its specific example includes polytetrafluoroethylene (PTFE), PVdF (polyvinylidene fluoride), PVdF-based copolymers such as PVdF-HFP (polyvinylidenefluoride-co-hexafluoropropylene, polyvinylidene fluoride-to-hexafluoropropylene), or two or more thereof. In particular, fluorine-containing adhesive can include polytetrafluoroethylene (PTFE). In addition, fluorine-containing adhesive can include only polytetrafluoroethylene, or in addition to polytetrafluoroethylene, can further include at least one selected from PVdF (polyvinylidene fluoride, polyvinylidene fluoride), and PVdF-based copolymers such as PVdF-HFP (polyvinylidenefluoride-co-hexafluoropropylene, polyvinylidene fluoride-to-hexafluoropropylene). The fluorine-free adhesive may include polyolefin, polyethylene oxide (PEO), or the like.

[0071] In general, an elastomer, often referred to as rubber, is a chemically cross-linked polymer. Since the density of the cross-linked structure of an elastomer is significantly lower than that of a thermosetting resin, the elastomer has a large elastic region between the cross-links, which gives the elastomer its elasticity. In this context, elasticity refers to the property of an object to stretch when pulled or pressed, and to try to return to its original state when the force is removed.

[0072] Fluoroelastomer (fluoro-elastomer) (fluorocarbon, fluorinated rubber) is a high-performance rubber that exhibits excellent resistance to high temperatures, ozone, weathering conditions, oxygen, mineral oils, fuels, hydraulic fluids, aromatic compounds, and various organic solvents and chemicals.

[0073] Fluoroelastomer is not particularly limited, and any known fluororubber for forming a molded body can be used. Specific examples of fluoroelastomer include vinylidene fluoride based rubber (FKM), tetrafluoroethylene propylene based rubber (FEPM), tetrafluoroethylene-perfluoromethyl vinyl ether based rubber (FFKM), tetrafluoroethylene based rubber (TFE), or the like. Such fluoroelastomers can be used alone or in combination.

[0074] Among the fluoroelastomers, vinylidene fluoride-based rubber (FKM) and tetrafluoroethylene propylene-based rubber (FEPM) may be more preferable.

[0075] Vinylidene fluoride rubber (FKM) includes vinylidene fluoride as a main component and is a fluoroelastomer with excellent heat resistance, oil resistance, chemical resistance, solvent resistance, processability, etc. Although FKM is not particularly limited, specific examples of FKM may include: a binary polymer including vinylidene fluoride and hexafluoropropylene; a binary polymer including vinylidene fluoride and tetrafluoroethylene; a ternary polymer including vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene; a quaternary polymer including ethylenediamine fluoride, hexafluoropropylene, tetrafluoroethylene and a vulcanization site monomer; or the like. Specific examples of commercially available products include: "Viton (registered trademark)" of DuPont Elastomers, "DAIEL (registered trademark) G" of Daikin Industries, Ltd., or the like. Among the examples listed above, a quaternary polymer including ethylenediamine fluoride, hexafluoropropylene, tetrafluoroethylene and a vulcanization site monomer is preferred. For example, the quaternary polymer is commercially available "Viton GBL-200S (DuPont Elastomers)".

[0076] Tetrafluoroethylene propylene rubber (FEPM) is an alternating copolymer based on tetrafluoroethylene (TFE) and propylene (P), and is a fluoroelastomer with excellent heat resistance, chemical resistance, polar solvent resistance, steam resistance, etc. Non-limiting examples of FEPM include: binary polymers including tetrafluoroethylene (TFE) and propylene (P); terpolymers including tetrafluoroethylene (TFE), propylene (P) and vinylidene fluoride (VDF); terpolymers including tetrafluoroethylene (TFE), propylene (P), and crosslinking site monomers (CSM). Specific examples of commercially available products including binary polymers of tetrafluoroethylene (TFE) and propylene (P) include "Aflas (registered trademark) 100" and "Aflas 150" from Asahi Glass Co., Ltd. Specific examples of commercially available products including terpolymers of tetrafluoroethylene (TFE), propylene (P) and vinylidene fluoride (VDF) include "Aflas 200" from Asahi Glass Co., Ltd. Specific examples of commercially available products including a terpolymer of tetrafluoroethylene (TFE), propylene (P), and a crosslinking site monomer (CSM) include "Aflas 300" from Asahi Glass Co., Ltd.

[0077] Tetrafluoroethylene-perfluoromethylvinyl ether rubber (FFKM) may include tetrafluoroethylene (TFE)-perfluoro(alkyl vinyl ether)-based copolymers, TFE-perfluoro(alkoxyalkyl vinyl ether)-based copolymers, or the like. Such copolymers may further include structural units derived from another perfluoro monomer. The perfluoro(alkyl vinyl ether) forming the tetrafluoroethylene (TFE)-perfluoro(alkyl vinyl ether)-based copolymer may have a C1-C10 alkyl group, and specific examples of perfluoro(alkyl vinyl ether) include perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether) and perfluoro(propyl vinyl ether), or the like, and preferably perfluoro(methyl vinyl ether). The perfluoro(alkoxyalkyl vinyl ether) forming the TFE-perfluoro(alkoxyalkyl vinyl ether)-based copolymer may include a C3-C15 group combined with a vinyl ether group (CF2=CFO-), and specific examples of perfluoro(alkoxyalkyl vinyl ether) include CF2=CFOCF2CF(CF3)OC n F 2n+1 CF2=CFO(CF2)3OC n F 2n+1 CF2=CFOCF2CF(CF3)O(CF2O) m C n F 2n+1 , or CF2 = CFO (CF2) 2OC n F 2n+1 In the above chemical formula, n may be 1-5, for example 1-3.

[0078] FFKM can be given crosslinking properties by copolymerization with crosslinking site monomers (by introducing structural units derived from crosslinking site monomers). In this article, "crosslinking site" refers to a site that can be crosslinked. For example, the crosslinking site can include a nitrile group, a halogen group (such as I, Br, or the like), a perfluorophenyl group, or the like.

[0079] A typical example of a crosslinking site monomer having a nitrile group as a crosslinking site is a perfluorovinyl ether containing a nitrile group. Specific examples of perfluorovinyl ether containing a nitrile group include: CF2=CFO(CF2) n OCF(CF3)CN (where n can be 2-4), CF2=CFO(CF2) n CN (where n can be 2-12), CF2=CFO[CF2CF(CF3)O] m (CF2) n CN (where n can be 2, m can be 1-5), CF2=CFO[CF2CF(CF3)O] m (CF2) n CN (where n can be 1-4, m can be 1-2), CF2=CFO[CF2CF(CF3)O] n CF2CF(CF3)CN (wherein n can be 0-4), or the like.

[0080] A typical example of a crosslinking site monomer having a halogen group as a crosslinking site is perfluorovinyl ether. Specific examples of perfluorovinyl ethers containing halogen groups include the examples of perfluorovinyl ethers containing nitrile groups listed above, wherein the nitrile groups are substituted with halogen groups. Specific examples of commercially available products of FFKM include "Kalrez" from DuPont.

[0081] According to an embodiment of the present disclosure, the fluoroelastomer may not include double bonds in its main chain. When the main chain of the fluoroelastomer does not include double bonds, the problem of oxidation at a high potential may be prevented.

[0082] In addition to active materials, conductive materials and binders, the electrode obtained according to the present disclosure further includes a fluoroelastomer having high elastic deformation performance in its electrode layer, thereby improving the performance of electrode fracture when impact or deformation occurs. In this way, an electrode with excellent flexibility can be provided.

[0083] When a non-fluorinated elastomer such as styrene butadiene rubber (SBR) including double bonds is present, oxidation occurs at a high potential, which may lead to a decrease in the performance of the battery. In the case of nitrile butadiene rubber (NBR) including double bonds, it can be used in batteries after hydrogenation to cleave the double bonds, but there is a limitation that the bending resistance cannot be improved.

[0084] The electrode according to the present disclosure includes a fluoroelastomer rather than a conventional, ie, non-fluoroelastomer. Therefore, the elastomeric structure does not include double bonds, thereby exhibiting excellent chemical and solvent resistance and achieving excellent bending resistance.

[0085] The flexibility of the electrode can be evaluated based on its bending resistance.

[0086] According to the present disclosure, the bending resistance of the electrode is 10 mm (Ф) or less. According to an embodiment of the present disclosure, the bending resistance of the electrode can be 8 mm (Ф) or less, 5 mm (Ф) or less, 2 mm to 10 mm (Ф), 2 mm to 8 mm (Ф), 2 mm to 5 mm (Ф), 2 mm to 4 mm (Ф), 4 mm to 5 mm (Ф), or 2 mm to 3 mm (Ф).

[0087] The bending resistance can be evaluated according to the method of the test standard JIS K5600-5-1. In particular, the bending resistance of the electrode can be determined by contacting the electrode with test bars having different diameters and lifting both ends of the electrode to determine whether cracks are generated and determining the minimum diameter at which no cracks are generated.

[0088] According to an embodiment of the present disclosure, the bending resistance of the electrode is evaluated by the following steps: preparing a rectangular electrode sample with a size of 100 mm×50 mm; preparing test rods with respective diameters of 2, 3, 4, 5, 6, 8, 10, 12, 16, 20, 25 or 32 mm, selecting the test rod with the largest diameter and bringing the electrode sample into contact with the test rod, and judging whether cracks are generated in the mixture film of the electrode sample when lifting both ends of the electrode sample; and if no cracks are generated in the previous step, selecting a test rod with the second largest diameter, and judging whether cracks are generated in the mixture film of the electrode sample in the same manner as in the previous step, repeating this step to determine the minimum diameter value of the test rod that will not cause cracks in the mixture film of the electrode sample as the bending resistance.

[0089] According to an embodiment of the present disclosure, the binder is fibrillated to combine the active material, the conductive material and the fluoroelastomer. The electrode may include a fibrillated binder as a means of combining the active material, the conductive material and the fluoroelastomer, and the fibrillated binder shows less cutting and has excellent elongation properties in the longitudinal direction compared to conventional non-fibrillated binders, thereby improving the flexibility of the electrode layer and the electrode including the electrode layer. The fibrillation process of the binder will be explained in more detail in the section of the method for manufacturing the electrode described below.

[0090] According to an embodiment of the present disclosure, the content of the active material may be 85 to 98 parts by weight, the content of the conductive material may be 0.5 to 5 parts by weight, the content of the binder may be 0.5 to 10 parts by weight, and the content of the fluoroelastomer may be 0.1 to 5 parts by weight.

[0091] In addition, the content of the active material may be 90 to 98 parts by weight, the content of the conductive material may be 0.5 to 5 parts by weight, the content of the binder may be 0.5 to 5 parts by weight, and the content of the fluoroelastomer may be 0.2 to 5 parts by weight.

[0092] When the content of active material, the content of conductive material, the content of binder and the content of fluoroelastomer satisfy the ranges defined above, the binder can be sufficiently fibrillated in the subsequent kneading step to form a mixture agglomerate, an electrode film can be easily obtained by molding the mixed powder formed by the pulverizing step, the physical properties of the electrode film can be ensured, the content of active material can be ensured to prevent the problem of capacity decrease, and sufficient conductivity can be ensured.

[0093] Meanwhile, a filler may be further introduced into the electrode layer as a component for suppressing electrode expansion as appropriate. The filler is not particularly limited as long as it is a fiber material and does not cause any chemical changes in the corresponding battery. Specific examples of the filler include: olefin polymers such as polyethylene or polypropylene; fiber materials such as glass fiber or carbon fiber; or the like.

[0094] According to an embodiment of the present disclosure, the weight ratio of the binder to the fluoroelastomer may be 40:60 to 80:20, 50:50 to 75:25, or 50:50 to 65:35. When the weight ratio satisfies the above defined range, the performance of the electrode breaking when impact or deformation occurs can be improved, thereby providing an electrode having excellent flexibility (bending resistance) and good handling performance.

[0095] The current collector is not particularly limited as long as it has high conductivity and does not cause any chemical changes in the corresponding battery. Specific examples of current collectors include stainless steel, aluminum, nickel, titanium, calcined carbon, copper, aluminum or stainless steel treated with carbon, nickel, titanium, silver, or the like. In addition, fine surface irregularities can be formed on the surface of the current collector to enhance the binding force with the positive electrode active material. The current collector can be used in various shapes including films, sheets, foils, nets, porous bodies, foams, nonwoven nets, or similar shapes.

[0096] In addition, the current collector can be coated with a conductive primer layer in whole or in part to reduce surface resistance and improve adhesion. In this article, the conductive primer layer can include a conductive material and a binder for the primer layer. The conductive material is not particularly limited as long as it has conductivity. For example, the conductive material can include: carbonaceous material, metallic material (metal powder or metal fiber), conductive whisker, conductive metal oxide, conductive polymer or the like. The carbonaceous material can include natural graphite, artificial graphite, graphene, carbon black, denka black, acetylene black, ketjen black, Super-P, channel black, furnace black, lamp black, thermal black, carbon nanotube, graphite nanofiber, carbon nanofiber or the like. The metal material may include copper, nickel, aluminum, silver, or the like, the conductive whisker may include zinc oxide whisker, calcium carbonate whisker, titanium dioxide whisker, silicon oxide whisker, silicon carbide whisker, aluminum borate whisker, magnesium borate whisker, potassium titanate whisker, silicon nitride whisker, silicon carbide whisker, aluminum oxide whisker, or the like, the conductive metal oxide may include titanium dioxide or the like, the conductive polymer may include a polyphenylene derivative or the like. These materials may be used alone or in combination.

[0097] The adhesive used for the primer layer may be a fluorine-based adhesive (including PVDF and PVDF copolymers) or an acrylic adhesive soluble in a solvent, and may include a water-based adhesive such as styrene butadiene rubber (SBR).

[0098] The porosity of the electrode layer of the electrode can be 20% to 50%, 20% to 45%, 20% to 40%, 20% to 35%, 22% to 30%, 20% to 28%, 20% to 26%, 23.1% to 27.4%, 23.1% to 24.8%, 23% to 26%, or 24.8% to 27.4%. The porosity can vary slightly depending on the effect of interest, etc.

[0099] When the porosity of the electrode layer satisfies the above defined range, wetting with the electrolyte can be promoted, thereby improving life characteristics, output characteristics, etc. In addition, since the volume required to achieve the same capacity does not increase, the energy density based on volume can be improved.

[0100] The porosity of the electrode layer can be obtained by subtracting the volume and weight of the current collector from the volume and weight of the electrode to determine only the apparent density of the mixture film, and by using the true density calculated based on the true density of each component and composition, according to the following formula:

[0101] Porosity (%) = {1-(apparent density / true density)} × 100

[0102] According to an embodiment of the present disclosure, the crystallinity of the binder in the electrode layer may be 10% or less.

[0103] According to an embodiment of the present disclosure, the crystallinity (Xc) of the adhesive can be determined by using differential scanning calorimetry (DSC) based on the temperature (peak temperature) at the point where the highest enthalpy occurs during crystallization. In particular, the crystallinity is calculated by dividing the melting enthalpy (β value) actually measured by DSC by the melting enthalpy (β melting heat at equilibrium) of a theoretically perfect crystal (crystallinity 100%), expressed in units of %, and can be calculated according to the following formula 1. In this article, in the case of known polymers, the melting enthalpy of theoretically perfect crystals can be referred to the "Polymer Handbook", and in the case of unknown materials or newly synthesized materials, the melting enthalpy of theoretically perfect crystals can be calculated by extending the extrapolation method of the crystallinity of two or more points.

[0104] [Formula 1]

[0105] Xc(%)=(β m / β m °)×100

[0106] According to an embodiment of the present disclosure, the binder includes a fluorine-containing binder, and the QBR (Quantified Binder Ratio) of the electrode layer may be 1.1 or less.

[0107] In this paper, QBR is defined as follows:

[0108] QBR=Bs / Bf,

[0109] Wherein Bs represents the average value of the fluorine content in the surface area of ​​the electrode layer within the range from the outermost surface of the electrode layer to 15% of the total thickness of the electrode layer, and Bf represents the average value of the fluorine content in the bottom area of ​​the electrode layer within the range from the electrode layer interface facing the current collector to 15% of the total thickness of the electrode layer.

[0110] Figure 1 is a schematic diagram showing an electrode according to an embodiment of the present disclosure. Figure 1The electrode 10 includes: an electrode current collector 12; and an electrode layer 11 located on the electrode current collector 12 and including an electrode active material and a binder. Herein, the electrode layer may further include a conductive material as described above as appropriate.

[0111] Based on the total thickness d of the electrode layer, the electrode layer 11 has an electrode layer surface area 11s within a range from the outermost surface of the electrode layer to 15% of the total thickness d of the electrode layer, and an electrode layer bottom area 11f within a range from the electrode layer interface facing the current collector to 15% of the total thickness d of the electrode layer.

[0112] In the mathematical formula of QBR, Bs represents the average value of the fluorine content in the electrode layer surface region 11s, and Bf represents the average value of the fluorine content in the electrode layer bottom region 11f.

[0113] In this article, QBR can be calculated by the following method.

[0114] First, the electrode whose QBR is to be determined is selected, and the cross section of the electrode is obtained by using argon ion milling. Next, the energy dispersive X-ray spectroscopy (EDS) detector of a scanning electron microscope (SEM) instrument is used to perform EDS mapping of each component in the electrode layer of the electrode cross section.

[0115] Then, a line profile is extracted from the EDS mapping results along the thickness direction of the electrode layer, and the average value Bs of the fluorine content of the fluorine-containing binder in the surface area of ​​the electrode layer and the average value Bf of the fluorine content of the fluorine-containing binder in the bottom area of ​​the electrode layer are extracted from the line profile results. Thereafter, QBR is calculated by using the following formula:

[0116] QBR=Bs / Bf

[0117] In this article, the electrode layer surface area is the area within the range of 15% of the total thickness d of the electrode layer from the outermost surface of the electrode layer along the thickness direction of the electrode layer, and the electrode layer bottom area is the area within the range of 15% of the total thickness d of the electrode layer from the electrode layer interface facing the current collector to the electrode layer.

[0118] Figure 2 Schematic diagram showing the calculation of the QBR value of the electrode layer. Figure 2, the X-axis represents the thickness of the electrode layer, that is, the distance from the surface to the current collector, and the Y-axis represents the intensity of the fluorine component. Line A represents the intensity of the fluorine component of the fluorine-containing binder extracted by EDS mapping of the fluorine component in the electrode layer of the electrode cross section, and line B represents a trend line showing the trend of line A, and is drawn by the LOWESS smoothing method, that is, smoothing by the Locally-Weighted Scatterplot Smoother mode.

[0119] The QBR value is a value showing the uniformity of the distribution of the fluorine-containing binder along the thickness direction of the electrode layer by the ratio of the content of the fluorine-containing binder contained in the surface region of the electrode layer to the content of the fluorine-containing binder contained in the bottom region of the electrode layer. Herein, the content of the fluorine-containing binder can be inferred from the fluorine component contained in the fluorine-containing binder.

[0120] The QBR value is 1.1 or less. According to an embodiment of the present disclosure, the QBR value may be 0.95 or more, 0.97 or more, 1.03 or less, 1.05 or less, or 0.95 to 1.05.

[0121] When the QBR value satisfies the above-defined range of 1.1 or less, there is no problem of an increase in the content of the fluorine-containing binder contained in the surface region of the electrode layer and the content of the fluorine-containing binder contained in the bottom region of the electrode layer due to the migration of the fluorine-containing binder. As a result, the distribution of the binder in the thickness direction of the electrode layer becomes uniform, and the content of the binder in the vicinity of the current collector is not reduced, so the adhesion between the current collector and the electrode layer is improved, and the conductivity and charge / discharge rate of the surface of the electrode layer are also improved.

[0122] Specific examples of fluorine-containing adhesives include polytetrafluoroethylene (PTFE), PVdF (polyvinylidene fluoride), PVdF-based copolymers such as PVdF-HFP (polyvinylidenefluoride-co-hexafluoropropylene), or two or more thereof. In addition, the fluorine-containing adhesive may include polytetrafluoroethylene alone, or a combination of polytetrafluoroethylene and at least one selected from PVdF (polyvinylidene fluoride) and PVdF-based copolymers such as PVdF-HFP (polyvinylidenefluoride-co-hexafluoropropylene).

[0123] The electrode layer can be derived from a dry electrode film. In this article, a dry electrode film refers to an electrode film obtained by a dry electrode manufacturing process without using a dispersion medium, which is different from a conventional wet electrode manufacturing process, which includes preparing a slurry by dissolving and / or dispersing an active material, a conductive material, and a binder in a dispersion medium such as water or an organic solvent, and applying the slurry to a current collector and then drying it. The obtained electrode film is then laminated on a current collector to provide a finished electrode. The method for manufacturing an electrode film and an electrode will be explained in more detail below.

[0124] In another aspect of the present disclosure, there is provided a method for manufacturing an electrode according to the present disclosure, the method comprising the steps of:

[0125] preparing a mixture comprising an active material, a conductive material, a binder, and a fluoroelastomer;

[0126] kneading the mixture at 70° C. to 200° C. under a pressure equal to or higher than ambient pressure to prepare a mixture mass;

[0127] pulverizing the mixture agglomerate to obtain a mixed powder for an electrode;

[0128] introducing a mixed powder for an electrode between a plurality of rollers to perform calendaring, thereby forming an electrode film; and

[0129] The electrode film is laminated onto the current collector.

[0130] Hereinafter, a method for manufacturing an electrode according to the present disclosure will be explained in more detail.

[0131] First, a mixture including an active material, a conductive material, a binder and a fluoroelastomer is prepared.

[0132] Herein, the mixing for preparing the mixture is carried out in such a way that the active material, the conductive material, the binder and the fluoroelastomer can be uniformly distributed. In addition, since the mixture is mixed in the form of a powder, any mixing process that can simply mix the components can be used without particular limitation, and the components can be mixed by various processes. However, since the electrode according to the present disclosure is manufactured by a dry process without using a dispersion medium, it can be mixed by a dry mixing process, and the components can be introduced into an instrument such as a mixer for mixing.

[0133] Furthermore, mixing may be performed in a mixer at 5,000 rpm to 20,000 rpm for 30 seconds to 2 minutes, and specifically, at 10,000 rpm to 15,000 rpm for 30 seconds to 1 minute to ensure uniformity.

[0134] According to an embodiment of the present disclosure, a super mixer may be used in the mixing step for preparing the mixture. Specifically, the mixing step may be performed in the super mixer at 1,000 rpm to 2,000 rpm for 5 to 10 minutes.

[0135] The binder is not particularly limited as long as it can be fibrillated by the step of preparing the mixed powder. The fibrillation refers to a process of finely dividing the polymer, and can be performed, for example, by using a mechanical shear force or the like. Specific examples of the binder are the same as those described above.

[0136] Next, the mixture is kneaded at 70° C. to 200° C. under a pressure equal to or higher than ambient pressure to prepare a mixture mass.

[0137] According to the prior art, high shear mixing, such as jet milling, is performed to fibrillate the binder. However, in this case, there is a problem that the active material is micronized by mixing and the resulting fibers may be cut. According to the present disclosure, this problem is solved by using a low shear kneading process instead of high shear mixing.

[0138] The kneading is not limited to a specific process. According to an embodiment of the present disclosure, the kneading may be performed by a kneader or the like.

[0139] The kneading step is a step of combining or connecting the active material, the conductive material and the fluoroelastomer while fibrillating the binder to form a mixture mass having a solid content of 100%. In addition, during the kneading step, the fluidity of the fluoroelastomer at 80° C. or higher can be improved and can be uniformly dispersed.

[0140] In particular, kneading can be controlled to a kneading rate of 10 rpm to 100 rpm. For example, the kneading rate can be controlled to be 20 rpm to 70 rpm within the range defined above. Kneading can be performed for 1 minute to 30 minutes.

[0141] For example, kneading can be carried out for 3 minutes to 10 minutes at a rate of 20rpm to 50rpm within the above defined range. Meanwhile, kneading can be controlled to a shear rate of 10 / s to 500 / s. According to an embodiment of the present disclosure, kneading can be carried out for 1 minute to 30 minutes, and the shear rate can be controlled to 30 / s to 100 / s.

[0142] Furthermore, the kneading step can be carried out at ambient pressure or at elevated pressure conditions, in particular pressure conditions above ambient pressure, at elevated temperature.

[0143] More specifically, kneading of the mixture may be performed at 70°C to 200°C, specifically 90°C to 150°C.

[0144] When kneading is performed at a low temperature exceeding the temperature range defined above, fibrillation of the binder and formation of agglomerates by kneading cannot be sufficiently performed during kneading. As a result, a film cannot be easily formed during calendering. On the other hand, when kneading is performed at an excessively high temperature, the binder may be rapidly fibrillated, and the resulting fibers may be cut by excessive shearing force, which is undesirable.

[0145] Furthermore, kneading may be performed at a pressure equal to or higher than ambient pressure, or at a pressure of 1 atm to 60 atm, 1 atm to 30 atm, 1 atm to 10 atm, 1 atm to 8 atm, 1.1 atm to 7 atm, or 1.1 atm to 6 atm.

[0146] When the pressure range defined above is met, the problem of the resulting fibers being cut and the density of the mixture mass being excessively increased due to the application of excessive shear force and pressure can be prevented. In other words, according to the present disclosure, the desired effect can be achieved when a low shear mixing step is performed at a high temperature under a pressure condition equal to or higher than the ambient pressure instead of high shear mixing.

[0147] Furthermore, according to an embodiment of the present disclosure, in order to improve the dispersibility of the fluoroelastomer, a portion of the active material or a portion of the conductive material may be preliminarily mixed and kneaded with the fluoroelastomer, and the preliminarily mixed and kneaded product may be further mixed and kneaded with the remaining electrode material.

[0148] Next, the mixture agglomerate is pulverized to obtain a mixed powder for an electrode.

[0149] In particular, the mixture mass prepared by kneading can be directly calendered. However, in this case, it is necessary to press the mixture mass to convert it into a film, so there is a problem that a uniform film cannot be obtained. Therefore, according to the present disclosure, the mixture mass is subjected to a pulverizing step. In other words, when the mixed powder for the electrode is too rough or agglomerated, a bridge is formed in the calendering step, resulting in defects such as pinholes in the film appearance, or a film with uneven surface properties. Therefore, a mixed powder for an electrode having a uniform size is obtained by pulverizing, and then calendered.

[0150] Herein, the pulverizing step can be performed by using a known pulverizing instrument, such as a blender or a grinder, but is not limited thereto. Specifically, the pulverizing step can be performed at a speed of 5,000 rpm to 20,000 rpm for 30 seconds to 10 minutes, more specifically, at a speed of 10,000 rpm to 18,000 rpm for 30 seconds to 2 minutes.

[0151] When the above-defined pulverization rate and time are met, pulverization can be sufficiently performed to form a powder having a size suitable for film formation and to prevent the problem of a large amount of fine powder being generated from the mixture mass. If necessary, a classification step for sieving powder having a size smaller or larger than a predetermined size can be performed.

[0152] According to an embodiment of the present disclosure, a cutter, a fine grinder, or the like can be used in the pulverizing step. In this article, the cutter can be used at 400rpm to 500rpm for a few seconds to coarsely crush the mixture mass obtained by kneading to a level of several millimeters. In addition, a fine grinder can be used to uniformly crush the coarsely crushed powder to a predetermined size or less, and can be operated at 3,000rpm to 8,000rpm.

[0153] Thereafter, the mixed powder for an electrode is introduced between a plurality of rolls to be rolled, thereby forming an electrode film.

[0154] Reference Figure 3a and Figure 3b , a step 100 of forming an electrode film is shown, wherein a plurality of rollers 110 are arranged to be spaced apart from each other. The mixed powder 120 for the electrode obtained by the previous step is introduced between adjacent rollers 110, and the rollers 110 are rotated in opposite directions. In this way, the mixed powder 120 is pressed and then subjected to a powder tableting step, so that it can be formed into a sheet or a film. Then, multiple calendering is performed to obtain an electrode film having a final target thickness.

[0155] According to an embodiment of the present disclosure, the interval between the rollers may be appropriately controlled in consideration of the size or physical properties of the electrode film to be obtained in the step of forming the electrode film. Figure 3b In, with Figure 3a In comparison, the interval between the second roller and the third roller and the interval between the fourth roller and the fifth roller can be controlled to be larger values.

[0156] In particular, the rolling includes processing the mixed powder for an electrode into a film shape. For example, the mixed powder for an electrode may be formed into a film having an average thickness of 50 μm to 300 μm.

[0157] For example, the calendering may be performed by using rolls facing each other. According to an embodiment of the present disclosure, the calendering may be repeated at least once, for example, repeatedly one to five times, three or four times, or four times.

[0158] Herein, the roll temperature may be 50°C to 200°C.

[0159] The roll speed ratio can be appropriately controlled depending on the roll size, the number of calendering times, the electrode film thickness, etc. For example, the roll speed ratio can be controlled within the range of 1 to 10 times, 1 to 8 times, 1 to 7 times, or 1.2 to 5 times.

[0160] Furthermore, the gap between a pair of rollers facing each other can be variably controlled depending on the thickness and density of a film to be obtained.

[0161] After the calendaring step is completed, a dry electrode film serving as an electrode mixture can be obtained. According to the prior art, the dry electrode film can also be referred to as a free standing film.

[0162] The obtained electrode film does not contain solvent and has almost no fluidity, so it can be easily handled and processed into a desired shape for manufacturing electrodes of various shapes. In addition, when using the electrode film according to the present disclosure to manufacture an electrode, the drying step for removing the solvent can be omitted, so the production processability of the electrode can be significantly improved, and the problems of the method for manufacturing dry electrodes according to the prior art, such as the brittleness of the active material or the cutting of the fibrillated binder, can be solved.

[0163] At the same time, according to an embodiment of the present disclosure, the porosity of the electrode film may be 20% to 50%. Within the range defined above, the porosity may be controlled to be 40% or less, or 30% or less. When the electrode film satisfies such a porosity range, wetting with an electrolyte may be promoted, thereby obtaining improvements in life characteristics, output characteristics, or the like. In addition, since the volume required to achieve the same capacity is not increased, the energy density based on volume may be increased. According to an embodiment of the present disclosure, the porosity may be obtained according to the following formula by determining the apparent density of the dry electrode film and using the true density calculated based on the true density of each component and composition:

[0164] Porosity (%) = {1-(apparent density / true density)} × 100

[0165] Afterwards, the electrode film is laminated onto the metal current collector.

[0166] The lamination step may be a step of pressing and adhering the electrode film obtained from the previous step to a current collector to a desired thickness. The lamination may also be performed by using a lamination roller, wherein the lamination roller may be maintained at a temperature of 25°C to -250°C.

[0167] According to an embodiment of the present disclosure, the compression ratio of the electrode film may be 30% to 50%, 35% to 50%, or 40% to 50%.

[0168] The compression ratio of the electrode film may be defined as the ratio of the compressed thickness of the electrode film at the time of lamination, and may be expressed by the following Formula 1:

[0169] [Formula 1]

[0170] Compression ratio (%) = T p / T1×100

[0171] Among them, T p represents the compressed thickness of the electrode film in the lamination step, and T1 represents the thickness of the electrode film before the lamination step.

[0172] According to the present disclosure, the lamination step can be controlled to meet a specific compression ratio. In this way, an electrode film having an appropriate density and porosity can be provided, and excellent adhesion between the electrode film and the current collector can be achieved.

[0173] When the electrode film satisfies a compression ratio of 30% to 50%, the pressure applied to the electrode film is sufficient so that the adhesion between the electrode film and the current collector can be improved. In addition, the problem of the electrode film being desorbed from the current collector after the lamination step can be prevented, and the problem of the electrode film density being undesirably increased, the porosity of the electrode film being reduced compared to the target porosity, or damage to the current collector can be solved.

[0174] According to an embodiment of the present disclosure, when the electrode film is laminated on both surfaces of the current collector, the compression ratio (%) of Formula 1 may be expressed by the following Formula 2:

[0175] [Formula 2]

[0176] 30≤(T1+0.5T c -0.5T gap ) / T1×100≤50

[0177] Where T1 represents the thickness of the electrode film before the lamination step, T c represents the thickness of the current collector, and T gap Indicates the interval between the first roller and the second roller.

[0178] Furthermore, the pressing ratio of the electrode film subjected to the lamination step may be 20% or less, 18% or less, 15% or less, 5% to 15%, 6% to 15%, 7% to 15%, or 9% to 13%.

[0179] Herein, the pressing ratio may be defined as a ratio of the thickness of the electrode film after the lamination step to the thickness of the electrode film before the lamination step, and may be represented by the following Formula 3:

[0180] [Formula 3]

[0181] Compression ratio (%) = (T1-T2) / T1×100

[0182] Here, T1 represents the thickness of the electrode film before the lamination step, and T2 represents the thickness of the electrode film after the lamination step.

[0183] When the pressing ratio satisfies the above-defined range, a resulting electrode film having appropriate density and porosity may be provided, and excellent adhesion between the electrode film and the current collector may be achieved.

[0184] The increase in apparent density before and after laminating the electrode film with the current collector can be expressed by the following formula 4:

[0185] [Formula 4]

[0186] Apparent density increase (%) = (D2-D1) / D1×100

[0187] Where D1 represents the apparent density of the electrode film before the lamination step (g / cm 3 ), D2 represents the apparent density of the electrode film after the lamination step (g / cm 3 ).

[0188] The increase in apparent density of the electrode film before and after lamination of the electrode film with the current collector may be 5% to 30%, 7% to 25%, or 10% to 20%.

[0189] D1 and D2, which represent the apparent density of the electrode film, may each vary depending on the type of active material. According to an embodiment of the present disclosure, when the active material is lithium nickel manganese cobalt oxide Li 1+x (Ni a Co b Mn c ) 1-x O2 (x is 0-0.03, a is 0.3-0.95, b is 0.01-0.35, c is 0.01-0.5, a+b+c=1), lithium nickel manganese cobalt oxide partially substituted by aluminum (lithium nickel manganese cobalt aluminum oxide) Li a [Ni b Co c Mn d Al e ] 1-f M 1 f O2 (where M 1is at least one selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S, 0.8 ≤ a ≤ 1.2, 0.5 ≤ b ≤ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≤ e ≤ 0.1, 0 ≤ f ≤ 0.1), or an analog, D1 and D2 can each be in the range of 2.75 g / cm 3 to 3.5 g / cm 3 .

[0190] Meanwhile, when the electrode film satisfies the increased range of the apparent density defined above, the adhesion between the electrode film and the current collector can be improved, and problems such as the porosity exceeding the target range or damage to the active material or the current collector can be prevented.

[0191] This increase in the apparent density before and after laminating the electrode film with the current collector can be calculated by measuring the weight and thickness of the electrode film before lamination, measuring the weight and thickness of the electrode after lamination, and calculating the weight and thickness of the film after subtracting the weight and thickness of the current collector.

[0192] In addition, the active material loading of the dry electrode film can be 3 mAh / cm 2 to 15 mAh / cm 2 , particularly 4 mAh / cm 2 to 10 mAh / cm 2 .

[0193] In this article, the active material loading is the value calculated according to Equation 5 below:

[0194] [Equation 5]

[0195] Active material loading (mAh / cm 2 ) = Capacity of active material (mAh / g) × Weight ratio of active material in dry electrode film (wt%) × Unit area weight of dry electrode film (g / cm 2 )

[0196] In addition, the interfacial resistance between the electrode film and the current collector can be 5 Ω·cm 2 or less, particularly 2 Ω·cm 2 or less. In this article, by the multi-probe (MP) resistance test method, after applying a current of 100 μA to the electrode, the interfacial resistance can be calculated by determining the resistance value between the dry electrode film and the current collector layer as the potential difference measured between multiple probes. When the interfacial resistance satisfies the range defined above, the subsequently obtained secondary battery can have improved performance.

[0197] Figure 42 is a schematic diagram showing a step of laminating an electrode film on both surfaces of a current collector according to an embodiment of the present disclosure. In other words, in the lamination step 200, the electrode film 230 obtained by the previous step can be pressed and adhered to the current collector 220 to a desired thickness by using a pair of lamination rollers 210, thereby providing a finished electrode 240.

[0198] In another aspect of the present disclosure, an electrode obtained by the method for manufacturing an electrode as described above is provided. In addition, a secondary battery including the electrode is provided, wherein the electrode is a positive electrode, and an electrode assembly including a positive electrode, a negative electrode and a separator is contained in a battery case (cylindrical case, prismatic case, bag or the like) together with a lithium-containing non-aqueous electrolyte. An energy storage system including the secondary battery as a unit cell is also provided.

[0199] Herein, since detailed structures of the secondary battery and the energy storage system are known to those skilled in the art, a detailed description thereof will be omitted in the present disclosure.

[0200] Meanwhile, according to an embodiment of the present disclosure, a system for manufacturing a dry electrode is provided. The system includes: a mixer configured to mix the components of an electrode mixture including an active material, a conductive material, a binder, and a fluoroelastomer; a kneader configured to knead the mixture of the components to form a mixture agglomerate; a pulverizer configured to pulverize the mixture agglomerate to form a mixed powder for an electrode; a calender configured to form a dry electrode film from the mixed powder for an electrode; and a laminating roller configured to place the dry electrode film on at least one surface of a current collector and perform lamination.

[0201] A blender is a mixer configured to mix the ingredients. As described above, the ingredients of the mixture may be mixed at a rate of 5,000 rpm to 20,000 rpm. The mixer may include a super mixer or the like.

[0202] The kneader is a device for fibrillating the binder and dispersing the components of the mixture according to the present disclosure, and the mixture can be obtained in the form of a mixture mass by kneading in the kneader. Herein, in order to obtain the results according to the present disclosure, the kneader can be set to a temperature of 70° C. to 200° C. or 90° C. to 180° C., and a pressure condition equal to or higher than ambient pressure, or a pressure of 1 atm to 60 atm, 1 atm to 30 atm, 1 atm to 10 atm, 1 atm to 8 atm, 1.1 atm to 7 atm, or 1.1 atm to 6 atm.

[0203] The pulverizer is configured to pulverize the obtained mixture mass to form a mixed powder for an electrode, and may include a blender or a grinder. The grinder may include a cutter, a fine grinder, or the like.

[0204] The calender is a device for molding the mixed powder for the electrode into a film shape. For example, the calender may include a pair of rollers facing each other, and the film thickness may be controlled by the interval between the rollers.

[0205] The laminating roller serves to attach and press the dry electrode film formed by the calendaring machine onto at least one surface of the current collector.

[0206] The porosity of the dry electrode film according to the present disclosure may be determined by a calendar and a lamination roll.

[0207] In other words, the system for manufacturing a dry electrode according to the present disclosure is characterized by including a kneader and a pulverizer.

[0208] The specific structures of the mixer, kneader, calender and laminating roller are known to those skilled in the art, and a detailed description thereof will be omitted here.

[0209] Embodiments will be described more fully below so that the present disclosure can be easily understood. However, the following embodiments can be implemented in many different forms and should not be interpreted as being limited to the exemplary embodiments set forth therein. Rather, these exemplary embodiments are provided so that the present disclosure will be thorough and complete, and the scope of the present disclosure will be fully conveyed to those skilled in the art.

[0210] Example 1

[0211] First, 950 g of lithium manganese oxide (Li2MnO2) (Posco, L25) as a positive electrode active material, 30 g of carbon black as a conductive material, and 13 g of polytetrafluoroethylene (PTFE) as a binder were introduced into a blender and mixed therein at 10,000 rpm for 1 minute to prepare a mixture.

[0212] Next, 7 g of FKM (Chemours, FKM10980) as a fluoroelastomer was added to the mixture, and the resulting mixture was introduced into a kneader.

[0213] The temperature of the kneading machine is stabilized at 150°C, the mixture is introduced into a pressurized kneading machine, and the kneading machine is operated at a rate of 40rpm for 5 minutes under a pressure of about 1.1atm to obtain a mixture mass. The mixture mass is introduced into a blender, crushed at 10,000rpm for 30 seconds, and classified by using a sieve with a hole size of 1mm to obtain a mixed powder for an electrode. Then, the resulting mixed powder for an electrode is introduced into a laboratory calender (roller diameter: 160mm, roller temperature: 100°C) to obtain an electrode film. Two pieces of electrode film are placed on both surfaces of an aluminum foil (thickness 19μm, coated with a conductive primer layer comprising carbon black and an acrylic adhesive mixed in a weight ratio of 5:6) and laminated by a compression roller maintained at 150°C to obtain an electrode (positive electrode).

[0214] The total thickness of the finished electrode was 343 μm, and the thickness of the active material layer formed on one surface of the active material layers provided on both surfaces of the current collector was 162 μm.

[0215] Example 2

[0216] A positive electrode was obtained in the same manner as in Example 1, except that 10 g of polytetrafluoroethylene (PTFE) was used as a binder and 10 g of FKM was used as a fluoroelastomer.

[0217] The total thickness of the finished electrode was 342 μm, and the thickness of the active material layer formed on one surface of the active material layers provided on both surfaces of the current collector was 162 μm.

[0218] Comparative Example 1

[0219] A positive electrode was obtained in the same manner as in Example 1, except that 20 g of polytetrafluoroethylene (PTFE) was used as a binder and 0 g of FKM was used as a fluoroelastomer.

[0220] The total thickness of the finished electrode was 345 μm, and the thickness of the active material layer formed on one surface of the active material layers provided on both surfaces of the current collector was 163 μm.

[0221] Comparative Example 2

[0222] A positive electrode was obtained in the same manner as in Example 1, except that 7 g of polytetrafluoroethylene (PTFE) was used as a binder and 13 g of FKM was used as a fluoroelastomer.

[0223] The total thickness of the finished electrode was 346 μm, and the thickness of the active material layer formed on one surface of the active material layers provided on both surfaces of the current collector was 164 μm.

[0224] Comparative Example 3

[0225] A positive electrode was obtained in the same manner as in Example 1, except that 0 g of polytetrafluoroethylene (PTFE) was used as a binder and 20 g of FKM was used as a fluoroelastomer. However, the resulting electrode film was easily broken, and thus a positive electrode sample could not be obtained.

[0226] Performance Evaluation

[0227] The positive electrode according to each of Example 1 and Comparative Example 1 and the secondary battery including each positive electrode were evaluated as follows. The results are shown in Table 1 below.

[0228] Herein, a secondary battery including the electrode according to each of Example 1 and Comparative Example 1 was obtained as follows.

[0229] Lithium metal was deposited on a copper foil to a thickness of 70 μm to obtain a negative electrode.

[0230] An electrode according to each of Example 1 and Comparative Example 1 was used as a positive electrode, and a polyethylene film (thickness: 20 μm) was interposed between the positive electrode and the negative electrode to obtain an electrode assembly. The electrode assembly was housed in a battery case, and a liquid electrolyte containing 1M LiPF6 was injected into the electrode assembly, the liquid electrolyte being dissolved in a solvent including ethylene carbonate, dimethyl carbonate, and diethyl carbonate mixed in a ratio of 1:2:1 (volume ratio), and then sealed to provide a secondary battery.

[0231] (1) Load capacity

[0232] The load was calculated according to the following formula:

[0233] Loading capacity (mAh / cm 2 ) = [capacity of active material (mAh / g)] × [weight ratio of active material in electrode film (wt%)] × [weight per unit area of ​​electrode film (g / cm 2 )]

[0234] (2) Porosity

[0235] The porosity of the electrode is obtained by subtracting the volume and weight of the current collector from the volume and weight of the electrode to determine only the apparent density of the electrode active material layer, and by using the true density calculated based on the true density of each component and composition, according to the following formula:

[0236] Porosity (%) = {1-(apparent density / true density)} × 100

[0237] (3) Bending resistance

[0238] According to the method of test standard JIS K5600-5-1, the bending resistance of each electrode is determined by bringing the electrode into contact with test bars having different diameters and lifting both ends of the electrode to judge whether cracks occur, and determining the minimum diameter at which no cracks occur.

[0239] In particular, the bending resistance of the electrode was evaluated by the following steps:

[0240] A rectangular electrode sample with a size of 100 mm × 50 mm was prepared;

[0241] preparing test rods each having a diameter of 2, 3, 4, 5, 6, 8, 10, 12, 16, 20, 25 or 32 mm, selecting the test rod having the largest diameter and bringing the electrode sample into contact with the test rod, and judging whether cracks are generated in the mixture film of the electrode sample when both ends of the electrode sample are lifted; and

[0242] If no cracks are generated in the previous step, select a test rod with the second largest diameter and judge whether cracks are generated in the mixture film of the electrode sample in the same manner as the previous step. Repeat this step to determine the minimum diameter value of the test rod that will not cause cracks in the mixture film of the electrode sample as the bending resistance.

[0243] For example, when a test rod with a diameter ranging from 32 mm to 3 mm was used, the electrode sample was brought into contact with the test rod, and both ends of the electrode sample were lifted, no cracks were generated in the mixed film of the electrode sample. However, when the electrode sample was brought into contact with a test rod with a diameter of 2 mm and both ends of the electrode sample were lifted, cracks were generated in the mixed film of the electrode sample. In this case, the bending resistance of the dry electrode was determined to be 3 mm (Ф), that is, the minimum diameter value of the test rod at which no cracks were generated in the mixed film of the electrode sample.

[0244] [Table 1]

[0245]

[0246] Referring to Table 1, it can be seen that the electrodes according to Examples 1 and 2 show improvement in breaking performance when impact or deformation occurs, compared with the electrodes according to Comparative Examples 1 to 3, thereby achieving excellent bending resistance.

Claims

1. An electrode, comprising: Electrode current collector; and an electrode layer, the electrode layer being disposed on the electrode current collector and comprising an active material, a conductive material, a binder and a fluoroelastomer; and The bending resistance of the electrode is 10 mm (Ø) or less. 2 . The electrode according to claim 1 , wherein the binder is fibrillated to bind the active material, the conductive material and the fluoroelastomer.

3. The electrode according to claim 1, wherein the fluoroelastomer comprises vinylidene fluoride based rubber (FKM), tetrafluoroethylene propylene based rubber (FEPM), tetrafluoroethylene-perfluoromethyl vinyl ether based rubber (FFKM), tetrafluoroethylene based rubber (TFE), or two or more thereof. 4 . The electrode according to claim 1 , wherein a weight ratio of the binder to the fluoroelastomer is 40:60 to 80:

20. The electrode according to claim 1 , wherein the bending resistance of the electrode is 2 mm to 8 mm (Ø). 6 . The electrode according to claim 1 , wherein the bending resistance of the electrode is evaluated according to the method of test standard JIS K5600-5-1.

7. The electrode according to claim 1, wherein the bending resistance of the electrode is evaluated by the following steps: A rectangular electrode sample with a size of 100 mm × 50 mm was prepared; preparing test rods each having a diameter of 2, 3, 4, 5, 6, 8, 10, 12, 16, 20, 25 or 32 mm, selecting the test rod having the largest diameter and bringing the electrode sample into contact with the test rod, and judging whether cracks are generated in the mixture film of the electrode sample when both ends of the electrode sample are lifted; and If no cracks are generated in the previous step, select a test rod with the second largest diameter and judge whether cracks are generated in the mixture film of the electrode sample in the same manner as the previous step. Repeat this step to determine the minimum diameter value of the test rod that will not cause cracks in the mixture film of the electrode sample as the bending resistance. The electrode according to claim 1 , wherein the binder has a crystallinity of 10% or less.

9. The electrode according to claim 1, wherein the binder comprises a fluorine-containing binder, the QBR (Quantified Binder Ratio) of the electrode layer is 1.1 or less, and the QBR is defined by the following formula: QBR=Bs / Bf, Wherein Bs represents the average value of the fluorine content in the surface area of ​​the electrode layer within a range from the outermost surface of the electrode layer to 15% of the total thickness of the electrode layer, and Bf represents the average value of the fluorine content in the bottom area of ​​the electrode layer within a range from the interface of the electrode layer facing the current collector to 15% of the total thickness of the electrode layer.

10. The electrode according to claim 1, wherein the conductive material comprises activated carbon, graphite, carbon black, Ketjen black, carbon nanotubes, or two or more thereof.

11. The electrode according to claim 1, wherein the binder comprises polytetrafluoroethylene (PTFE). 12 . The electrode according to claim 1 , wherein the active material is a positive electrode active material or a negative electrode active material.

13. The electrode according to claim 1, wherein the active material is contained in an amount of 80 to 98 parts by weight, the conductive material is contained in an amount of 0.5 to 10 parts by weight, the binder is contained in an amount of 0.5 to 5 parts by weight, and the fluoroelastomer is contained in an amount of 0.1 to 5 parts by weight.

14. The electrode of claim 1, wherein the current collector further comprises a conductive primer layer on at least one surface thereof.

15. The electrode of claim 1, wherein the electrode layer is derived from a dry electrode film.

16. A method for manufacturing an electrode as defined in claim 1, said method comprising the steps of: preparing a mixture comprising an active material, a conductive material, a binder, and a fluoroelastomer; kneading the mixture at 70° C. to 200° C. under a pressure equal to or higher than ambient pressure to prepare a mixture mass; crushing the mixture agglomerate to obtain a mixed powder for an electrode; introducing the mixed powder for an electrode between a plurality of rollers for rolling to form an electrode film; and The electrode film is laminated onto a metal current collector.

17. The method for manufacturing an electrode according to claim 16, wherein the step of kneading the mixture to prepare a mixture mass is performed in a kneader under a pressure equal to or higher than ambient pressure.

18. The method for manufacturing an electrode according to claim 16, wherein a pressing ratio of the electrode film is 20% or less. 19 . A secondary battery comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein at least one of the positive electrode and the negative electrode is an electrode as defined in any one of claims 1 to 15 .

20. An energy storage system comprising the secondary battery as defined in claim 19 as a unit battery.

Citation Information

Patent Citations

  • System for controlling smart street light and method there of

    KR1020220049213A